Efektivitas Media Leaflet dalam Promosi Kesehatan Perilaku Hidup Bersih dan Sehat (PHBS) : Literature Review - Mira Azmi Agustina; Lilis Lismayanti (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Clean and Healthy Living Behavior (PHBS) is one of the promotive and preventive efforts to improve public health status. Low public awareness regarding the implementation of PHBS remains a health problem in many regions. Health promotion using leaflet media is considered an effective educational method because it is easy to understand and can be read repeatedly by the community. This study aims to determine the effectiveness of health promotion using leaflet media in improving community knowledge and behavior regarding PHBS. The research method used a systematic literature review based on PRISMA 2020 guidelines by analyzing 15 national and international journals from 2015–2025. The results showed that leaflet media effectively improved community knowledge regarding hand washing, use of healthy latrines, waste management, environmental hygiene, physical activity, and healthy lifestyles. Leaflet media also helped increase community participation in maintaining environmental cleanliness and preventing infectious diseases. Therefore, health promotion using leaflets can be an effective educational strategy in improving PHBS implementation in the community